Sledgehammer: women's imprisonment at the millennium / Pat Carlen. - Carlen, Pat (Macmillan, 1998)
Readers will find that this is a compelling and compassionate analysis of the penal control of women at the end of the 20th century. It is the first critique of women's imprisonment in Britain to include materials from interviews with prison staff.